A new Stumpffia (Amphibia: Anura: Microhylidae) from the Ranomafana region, south-eastern Madagascar - Ndriantsoa, Serge H.; Riemann, Jana C.; Vences, Miguel; Klages, Johannes; Raminosoa, Noromalala R.; Rödel, Mark-Oliver; Glos, Julian (Zootaxa, 2013)
We describe a new species of small-sized frogs from degraded rainforest patches in the southern central east of Madagascar. Stumpffia miery sp. nov. has a snout-vent length of 13–15 mm and can be distinguished from all other nominal species of Stumpffia by its body size and absence of toe reduction combined with length reduction of fingers I, II and IV in external view. The advertisement call is a single tonal chirping note that ranges in duration between 51–88 ms and is emitted after relatively regular inter-note intervals (duration of 2679–4247 ms, call repetition rate 0.3/sec, frequency range 7700–8300 Hz, dominant frequency 7751–8225 Hz). Its type locality is the Ambolo forest fragment close to Ranomafana village in southeastern Madagascar. Molecular data from DNA sequences of one mitochondrial and one nuclear gene indicate a high divergence from all nominal species of Stumpffia, suggesting that it represents a strongly differentiated independent evolutionary unit. Stumpffia miery sp. nov. is apparently able to tolerate some degree of habitat degradation and therefore is probably not threatened with extinction.